High-performance dye-sensitized solar cell based on an electrospun poly(vinylidene fluoride-co-hexafluoropropylene)/cobalt sulfide nanocomposite membrane electrolyte. Issue 64 (12th July 2015) - Vijayakumar, E.; Subramania, A.; Fei, Zhaofu; Dyson, Paul J.
<x xml:space="preserve">Abstract</x> Electrospun PVdF-HFP/CoS (1 wt%) nanocomposite membrane prepared by electrospinning technique.